EEG in asymptomatic relatives of idiopathic epilepsy; a prospective study. (3rd June 2015) - Duaa, BM; Boelman, C; Brunga, L; Minassian, BA; Andrade, D
Abstract : Introduction: The mainstay of diagnosis in Idiopathic Epilepsies (IE) is the electroencephalogram (EEG). The characteristic EEG of each syndrome is an electrographic endophenotype of the larger clinical phenotype of each and more directly associated with potential gene defects than the full phenotype. Endophenotypes represents primary abnormalities elicited by the gene defect, which, in some patients, blossom into full seizures. Revealing the percentage of abnormal EEGs in asymptomatic relative of patients with IE may help to describe the mode of inheritance that would help the ongoing genetics studies to discover the pathologic gene defect. Method: This is a prospective cohort study to identify the percentage of abnormal EEG in asymptomatic first-degree relatives of patients with IE Results: 20 out of 141 EEGs (14%) of first-degree relatives were abnormal. The abnormalities included generalized polyspikes and waves, generalized 3-Hz spike and waves or centro-temporal spikes in 50% of the abnormal EEGs. 50% of the abnormalities were nonspecific. Conclusion: These results may indicate that the EEG endophenotypes in IEs do not follow a Mendelian pattern of inheritance. Nevertheless, the EEG endophenotype is relatively common and thus genetically simpler than the full epilepsy, which will aid in gene identification